Efficiency of agricultural production in the Poltava region and areas of improvement mechanisms of its development - Пісоцький, А. А. (Scientific Progress & Innovations, 2012)
The analysis of the level, dynamics and efficiency of agricultural production in the Poltava region. The organizational and economic mechanism to support the development of agricultural entrepreneurship at regional level that should be part of a national program of development of agrarian sector of Ukraine. A process to apply and program-target approach for the formation mechanism of state support for agricultural entrepreneurship at regional level as an integrated system.